2022
DOI: 10.1128/mbio.01420-22
|View full text |Cite
|
Sign up to set email alerts
|

S. cerevisiae Cells Can Grow without the Pds5 Cohesin Subunit

Abstract: Sister chromatid cohesion is vital for faithful chromosome segregation, chromosome folding into loops, and gene expression. A multisubunit protein complex known as cohesin holds the sister chromatids from S phase until the anaphase stage.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…In a remarkable convergence of studies, however, deletion of CLN2 was found to promote the viability of both eco1Δ rad61Δ at 37°C and pds5Δ elg1Δ cells (83,84). The latter study provided evidence that CLN2 deletion increased Mcd1 levels, such that simply elevating Mcd1 protein levels was sufficient to render viable pds5Δ elg1Δ double mutant cells (83).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In a remarkable convergence of studies, however, deletion of CLN2 was found to promote the viability of both eco1Δ rad61Δ at 37°C and pds5Δ elg1Δ cells (83,84). The latter study provided evidence that CLN2 deletion increased Mcd1 levels, such that simply elevating Mcd1 protein levels was sufficient to render viable pds5Δ elg1Δ double mutant cells (83).…”
Section: Resultsmentioning
confidence: 96%
“…Defects in cohesin regulation are also tightly correlated with several forms of cancer (8082). Despite the importance of cohesin functions, little is known regarding the regulation of cohesins early during the cell cycle, but recent findings confirm that MCD1 expression may be a critical component (83,84). In this study, we identify FDO1 as a novel regulator of MCD1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-recombinase Srs2 helicase recruited by SUMOylated PCNA was recently suggested to work at replication forks to support the viability of elg1 Δ pds5 Δ cells with increased levels of Scc1 (ref. 25 ). We indeed observed that elg1 Δ wpl1 Δ pds5 Δ cells rely on Srs2 for viability when Rad51 recombinase is expressed.…”
Section: Resultsmentioning
confidence: 99%
“…Pds5 is essential for cell viability, and in its absence, cohesion is lost. A new yeast study showed that cells can live without Pds5 under one of two conditions - overexpression of Mcd1 or an accumulation of the loading clamp PCNA on chromosomes ( Choudhary et al, 2022 ). These modifications stabilize cohesin on chromatin.…”
Section: Open Questions and Concluding Remarksmentioning
confidence: 99%